KONSEP 3 IN 1 IN THE LAND ACQUISITION UNTUK TANAH ASET DESA SEBAGAI KEKAYAAN ASLI YANG SAH - Satria Wira Yudha; Mohammad Saleh (Jurnal HUKUM BISNIS, 2022)
In the public interest, including the interests of the nation and state as well as the common interests of the people, land rights can be revoked by providing appropriate compensation according to the method regulated by law. The case that occurred was that the residents of Kapru Hamlet, Gunungsari Village, Bumiaji District, Batu City felt disadvantaged after finding that one of the Village Treasury Lands (TKD) was controlled by individuals. The formulation of the problem in this study is how legal efforts can be taken by the residents of Gunungsari Village to save village land assets from individual parties based on the 3 in 1 in the Land Acquisition concept. The research method in studying this problem is normative legal research. The concept of 3 in 1 in the Land Acquisition in land acquisition for development is a land acquisition activity from beginning to end or from upstream to downstream which ultimately leads to three points, namely the start point, decision point and product point. Individuals who control the land to be used as land can file an objection and verification and improvement will be carried out in order to obtain legal certainty regarding ownership rights and land objects. However, if it is Village Treasury Land, the individual does not receive compensation. Keywords: Land Procurement, Public Interest, .Village Land